Impact of Shield Tunnel Construction on Adjacent Railway Bridge: Protective Measures and Deformation Control - Wen Liu; Lu Zhao; Xiang-Chuan Yao; Hai-Ao Zheng; Wen-Li Liu (Buildings)
With the rapid development of urban rail transit networks, constructing shield tunnels often requires passing underneath existing buildings, which can potentially impact their safety. This study examined the impact of constructing a double-line shield tunnel underneath a railway bridge on the adjacent pile foundation via numerical simulation. Protective measures, including construction parameter control, grouting methods, monitoring, and early warning systems, were implemented to mitigate impacts. The results indicated that the bridge deformation fell within acceptable limits, with maximum horizontal and longitudinal displacements of 0.06 mm and a maximum vertical displacement of −0.31 mm. The railway bridge pile foundation experienced maximum horizontal and longitudinal displacements of 0.47 mm and vertical displacements of −0.23 mm during construction. Enhanced construction quality control and monitoring effectively controlled deformation to ensure the railway safety. This study provides valuable guidance for similar projects and future urban rail transit developments.